Validating the accuracy of a novel virtual reality platform for determining implant orientation in simulated primary total hip replacement - Daniel Howgate; Michael Oliver; Julie Stebbins; Patrick Garfjeld Roberts; Ben Kendrick; Jonathan Rees; Stephen Taylor (Digital Health, 2022)
Introduction Accurate acetabular cup and femoral stem component orientation are critical for optimising patient outcomes, reducing complications and increasing component longevity following total hip replacement (THR). This study aimed to determine the accuracy of a novel virtual reality (VR) platform in assessing component orientation in a simulated THR model. Methods The VR platform (HTC Vive Pro® system hardware) was compared against the validated Vicon® optical motion capture (MoCap) system. An acetabular cup and femoral stem were manually implanted across a range of orientations into pelvic and femur sawbones, respectively. Simultaneous readings of the acetabular cup operative anteversion (OA) and inclination (OI) and femoral stem alignment (FSA) and neck anteversion (FNA) were obtained from the VR and MoCap systems. Statistical analysis was performed using Pearson product-moment correlation coefficient (PPMCC) (Pearson’s r) and linear regression (R 2 ). Results A total of 55 readings were obtained for the acetabular cup and 68 for the femoral stem model. The mean average differences in OA, OI, FSA and FNA between the systems were 3.44°, −0.01°, 0.01° and −0.04°, respectively. Strong positive correlations were demonstrated between both systems in OA, OI, FSA and FNA, with Pearson’s r = 0.92, 0.94, 0.99 and 0.99, and adjusted R 2  = 0.82, 0.9, 0.98 and 0.98, respectively. Conclusion The novel VR platform is highly accurate and reliable in determining both acetabular cup and femoral stem component orientations in simulated THR models. This adaptable and cost-effective digital tracking platform may be modified for use in a range of simulated surgical training and educational purposes, particularly in orthopaedic surgery.